Financial management engagement and small and medium-sized businesses in eThekwini municipality, South Africa - Kansilembo Aliamutu; Msizi Mkhize (Economics, Management and Sustainability, 2024)
Small and medium-sized businesses are widely recognised as the cornerstone of growth in emerging and middle-class countries, and South Africa is no different. They generate many job possibilities and salaries for many individuals who live in cities, making them an essential component of average national production. The main objective of the research was to examine the level to which Small and Medium-sized businesses in the eThekwini Municipality used financial management. The research project used a quantitative method to collect and analyse data from the field. The survey included 60 participants from various small and medium-sized businesses in eThekwini. Proprietors and managers of small and medium-sized businesses were among those who responded. The rate at which organisations implement systems that effectively organise their money was a crucial component in analysing the financial management engagements of small and medium-sized businesses. This can be assessed in various ways, including distributing closed-ended surveys to responders. As a result, the proprietors of small and medium-sized businesses were prompted to score their companies based on the level to which financial preparation strategies were implemented and the funding sources. The research found that small and medium-sized businesses in the research areas did not develop long-term financial strategies that included investments in non-current assets, shares, stocks, and real estate initiatives. Small and medium-sized businesses must establish trustworthy systems for accounting information, disclose and analyse their financial challenges regularly, and advocate for laws that make it simpler for small and medium-sized businesses to obtain inexpensive financing. Since small and medium-sized businesses are recognised as contributing significantly to national economic growth, they must keep growing.